Model Komunikasi Developer Syariah dalam Solusi Peningkatan Ekonomi Islam - Ramlan Indra Jaya (Jurnal Al-Hikmah, 2022)
The house is one of the most important needs in human life, as well as food and clothing. The house is one of the most important needs in human life, especially in the household. The house has an important meaning for every family because the house is a basic need where the family gathers. Government action for the welfare of the people. the role of the developer as a provider and housing development that can make this happen. So in this paper, we will discuss more deeply how the Sharia developer communication model in solutions to improve the Islamic economy. In conclusion, we can understand that the definition of a developer is the activity of a person in the property business. Which in the process Developers build, rent and buy property land which is then rebuilt housing and settlements which are then resold to the community. The functions and objectives of the developer include: conducting financing and negotiating to realize a development, creating the right residential concept, Development of housing/settlement by the developer so that a life order can be formed which contains physical elements in the sense that settlements are a forum for activities where communities meet to interact. Social interaction with the community, can be said as the embodiment of identity, housing / residential housing by the developer can also be a place of intimacy, a sense of belonging, a sense of togetherness, warmth, love and security, housing by a residential developer can be used as a root and continuity of life that where home is a place to return to the roots and foster a sense of continuity in the thread, process into the future. The Role of Developers in improving the Islamic economy: 1)Developer as an extension of the Government 2) Ease of Payment System 3) The formation of a new civilization 4) Welfare of society by fulfilling one of the basic needs. 5) Creating great job opportunities to improve the quality of people's lives. Housing development is aimed at realizing settlements that are functionally accessible.